Global climatology based on the ACE-FTS version 3.5 dataset: Addition of mesospheric levels and carbon-containing species in the UTLS. (January 2017) - Koo, Ja-Ho; Walker, Kaley A.; Jones, Ashley; Sheese, Patrick E.; Boone, Chris D.; Bernath, Peter F.; Manney, Gloria L.
Abstract: In this paper, we present a new climatology based on the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) version 3.5 data set from February 2004 to February 2013. This extends the ACE-FTS climatology to include profile information in the mesosphere and carbon-containing species in the upper troposphere and lower stratosphere. Climatologies of 21 species, based on nine years of observations, are calculated, providing the most comprehensive and self-consistent climatology available from limb-viewing satellite measurements. Pressure levels from the upper troposphere to the mesosphere and lower thermosphere are included with 3 to 4 km vertical resolution up to 10 −4 hPa ( 105 km). Volume mixing ratio values are filtered prior to the climatology estimation using the ACE-FTS data quality recommendations. The multi-year mean climatology contains zonal mean profiles for monthly and three-monthly (DJF, MAM, JJA, and SON) periods. These are provided with 5-degree spacing in either latitude or equivalent latitude. Also, the local daytime and nighttime distributions are provided separately for nitrogen-containing species, enabling diurnal differences to be investigated. Based on this climatology, examples of typical spatiotemporal patterns for trace gases in the mesosphere and for carbon-containing gases in the upper troposphere and lower stratosphere are discussed. Highlights: A new global climatology has been produced from the ACE-FTS v3.5 data set. Fields are on pressure levels that extend from upper troposphere up to mesosphere. Seven carbon-containing species are now provided with 14 ACE-FTS baseline gases.